Operator assessment versus core laboratory adjudication of recanalization following endovascular treatment of acute ischemic stroke: a systematic review and meta-analysis. (26th September 2022) - Ibrahim, Mohamed K; Shehata, Mostafa A; Ghozy, Sherief; Bilgin, Cem; Jabal, Mohamed Sobhi; Heiferman, Daniel M; Kadirvel, Ramanathan; Kallmes, David F
Abstract : Background: Successful recanalization after endovascular thrombectomy serves as the primary endpoint in clinical trials and is a crucial predictor of long-term outcomes. Radiographic outcomes for various interventions have been shown to vary based on the type of interpreter, including the site interventionalist compared with an independent reader. Objective: To compare angiographic outcomes in stroke thrombectomy procedures based on the type of reader. Methods: A systematic literature search was conducted in Medline, EMBASE, Scopus, and Web-of-Science through February 2022. We included primary studies that reported core laboratory-read and operator angiographic outcomes after mechanical thrombectomy for ischemic stroke. Furthermore, study-defined successful recanalization data were collected. Results: Eight studies were included with 4797 patients, 51.2% of whom were male. Four thousand, four hundred and thirty-one patients had core readings, and 4211 had operator readings. Study-defined successful recanalization was significantly higher for operator (84%, 3543/4211) examinations than for core laboratory-read (78.4%, 3476/4431) examinations (p<0.001; OR=1.462, 95% CI 1.175 to 1.819). The modified Thrombolysis in Cerebral Infarction (mTICI) scale score of ≥2 b was higher for operator (85%, 3341/3929) examinations than for core laboratory-read (78.6%, 3107/3952) examinations (p<0.001; OR=1.349, 95% CI 1.071 to 1.701). mTICI 3 was significantly higher for operator (54.6%, 1000/1832) examinations than for core laboratory-read (39.9%, 731/1832) examinations (p<0.001; OR=1.823, 95% CI 1.598 to 2.081). Conclusion: Operator angiographic reads are statistically significantly higher than core laboratory-read readings following stroke thrombectomy, especially for complete recanalization. These differences should be considered when interpreting reports of angiographic outcomes after thrombectomy.